Detachable structure bonding hot melt adhesive based on multi-element synergistic self-repairing polyurethane and synthesis method of detachable structure bonding hot melt adhesive
Through the synthesis method based on multivariate synergistic self-healing polyurethane, the ratio of prepolymer to AD and DBD is adjusted, and the problem of difficult balance between ductility and bonding strength of the adhesive is solved, and an adhesive with high strength, high ductility and self-healing function is achieved.
Patent Information
- Application Number
- CN202510070206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Existing adhesives have difficulty in achieving a balance between ductility and bonding strength, resulting in problems of embrittlement under stress and bonding failure.
The synthesis method based on multivariate synergistic self-healing polyurethane is adopted to adjust the ratio of prepolymers to AD and DBD, and change the length and aggregation state of the molecular chain to achieve a balance between cohesion energy and adhesion.
The adhesive has excellent shear strength, tensile strength, elongation of break and tensile toughness at room temperature, and has self-healing function at high temperature, and the tensile strength self-healing efficiency reaches more than 95%.
Smart Images

Figure CN119799258A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hot melt adhesives, and in particular relates to a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane and a synthesis method thereof. Background Art
[0002] Adhesive materials are indispensable in modern life, ingeniously integrating complex structures such as buildings, electronic devices, industrial vehicles and aircraft into a whole. As the demand for adhesive materials increases, their application scenarios are becoming more and more complex. Currently, adhesives on the market usually have only ductility or rigidity, and achieving an effective balance between the two remains a challenge. Ductility is common in most low-modulus materials, which have weak molecular interactions and high chain mobility, allowing adhesives to withstand stretching and disperse mechanical stress, effectively preventing sudden adhesive failure. However, the bonding strength of these adhesives is usually low and difficult to resist significant external forces. At the same time, high bonding strength relies on strong covalent bonds and stable cross-linking networks. Although strong adhesives have high cohesive strength and can withstand heavy loads, their embrittlement under stress may cause sudden strength loss and fracture. An ideal adhesive should strike a balance between ductility and strength, as these two properties often restrict each other. Therefore, developing an adhesive that combines removability, high ductility and high strength is a major technical challenge in practical applications.
[0003] The bonding strength of adhesives is significantly affected by two key factors: cohesive strength and adhesive strength. The cohesive strength of adhesives is closely related to their mechanical properties and adhesive action. The cross-linking network involves the formation of covalent or non-covalent interactions between molecular chains and is one of the effective means to improve cohesive strength. In addition, traditional adhesives introduce non-covalent interaction forces as dynamic sacrificial bonds, including hydrogen bonds, host-guest interactions, and ion-dipole interactions, which effectively dissipate mechanical energy during the bonding process. However, these forces may gradually weaken over time and with changes in pH, resulting in reduced bonding strength. To address this issue, researchers have developed new strong adhesives based on dynamic covalent networks, however, in most cases, it still does not provide strong adhesion. Adhesion refers to the bond strength formed between the adhesive and the adherend surface, which is affected by the energy parameters of the adhesive on the substrate. This includes molecular-level adhesion, local chemical properties, microscopic surface roughness, and macroscopic mechanical properties. When adhesives are used in load-bearing applications, too high cohesive strength may lead to delamination, while too high adhesive strength may lead to internal fracture. Therefore, the optimal bonding strength depends on the balance between strong cohesive molecular interactions and strong adhesion to the substrate.
[0004] Based on this understanding, the present invention designs a series of detachable structural bonding hot melt adhesives based on multi-synergistic self-healing polyurethane. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane and a synthesis method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane, comprising the following steps:
[0008] (1) putting polytetramethylene ether glycol (PTMEG) or polytrimethylene ether glycol (PO3G) into a reaction kettle, heating to 120° C. and vacuum dehydrating for 1 hour, then lowering the temperature to 80° C., adding isophorone diisocyanate (IPDI) or 4,4-diisocyanate dicyclohexylmethane (HMDI) and stirring for 1 hour under a nitrogen atmosphere, and finally adding a catalyst dibutyltin dilaurate (DBTDL) for prepolymerization for 3 hours to obtain a prepolymer;
[0009] (2) 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide (AD) dissolved in a diluent is added into a reaction kettle until the -NCO peak in FTIR disappears;
[0010] (3) 3,4-dihydroxybenzaldehyde (DBD) was added, and the reaction was maintained at 80°C under a nitrogen atmosphere. After 8 hours, the uniform viscous liquid was poured into a polytetrafluoroethylene mold, maintained at 80°C for 48 hours, and then vacuum dried for 12 hours to obtain a detachable structural bonding hot melt adhesive based on multi-component synergistic self-healing polyurethane (PU-PADx), wherein x represents the molar ratio of prepolymer to AD in the system.
[0011] Preferably, in step (1), the number average molecular weight Mn of the polytetramethylene ether glycol (PTMEG) or polytrimethylene ether glycol (PO3G) is 850 to 1500 g / mol.
[0012] Preferably, in step (1), the molar ratio of polytetramethylene ether glycol (PTMEG) or polytrimethylene ether glycol (PO3G) to isophorone diisocyanate (IPDI) or 4,4-diisocyanate dicyclohexylmethane (HMDI) is 1:2.
[0013] Preferably, in step (1), the molar ratio of the polytetramethylene ether glycol (PTMEG) or polytrimethylene ether glycol (PO3G) to the catalyst dibutyltin dilaurate (DBTDL) is 1:10. -5 .
[0014] Preferably, in step (2), the diluent is a mixture of one or more of N,N-dimethylformamide, cyclohexanone, N,N-dimethylacetamide, and N-methylpyrrolidone, and the mass ratio of 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide (AD) to the diluent is 1:4.
[0015] Preferably, in step (2), the molar ratio x of the prepolymer to 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide (AD) is 1:1.2 to 2.0, most preferably 1:1.4.
[0016] Preferably, in step (3), the molar ratio of the prepolymer to 3,4-dihydroxybenzaldehyde (DBD) is 1:0.4-2.0, most preferably 1:0.8.
[0017] Preferably, the room temperature aluminum-aluminum shear strength of the hot melt adhesive synthesized by the above synthesis method is 4.25-14.23 MPa, the shear strength retention rate after repeated bonding for 6 times is more than 93.04%, and it exhibits excellent mechanical properties at 0-55°C and on a variety of substrates, with a tensile strength of 11.4-24.5 MPa, an elongation at break of 234.3-743.3%, and a tensile toughness of 12.4-66.5 MJ / m 3 , treated at 80℃ for 30 minutes, the self-healing efficiency of tensile strength reached more than 95%.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The polytetramethylene ether glycol (PTMEG) or polytrimethylene ether glycol (PO3G) prepolymer terminated with isophorone diisocyanate (IPDI) or 4,4-diisocyanate dicyclohexylmethane (HMDI) of the present invention is intentionally extended by different contents of 4,4'-diaminodiphenyl disulfide or 2,2'diaminodiphenyl disulfide (AD) and terminated with 3,4-dihydroxybenzaldehyde (DBD) in order to manipulate the chain length and aggregation state thereafter. By adjusting the ratio of the prepolymer to AD and DBD, the length and aggregation state of the molecular chain are changed, and an effective balance between cohesive energy and adhesion is achieved.
[0020] 2. The hot melt adhesive synthesized by the present invention has excellent shear strength, tensile strength, elongation at break and tensile toughness. The tensile strength reaches 11.4-24.5MPa, the elongation at break reaches 234.3-743.3%, and the tensile toughness reaches 12.4-66.5MJ / m 3These properties not only highlight its excellent bonding performance in practical applications, but also provide a promising strategy for developing the next generation of tougher materials and adhesives. With its excellent toughness and high strength, PU-PADx hot melt adhesive provides innovative solutions for the environmental protection and high-precision processing industries.
[0021] 3. The hot melt adhesive synthesized by the present invention not only has high bonding strength and re-bonding ability, but also exhibits excellent bonding performance on various metal substrates and wooden boards, greatly expanding the application range of the adhesive. The room temperature aluminum-aluminum shear strength of the hot melt adhesive is 4.25-14.23 MPa, and the shear strength retention rate after repeated bonding for 6 times is more than 93.04%. It exhibits excellent mechanical properties at 0-55°C and on a variety of substrates, which is better than most reported reusable adhesives.
[0022] 4. The hot melt adhesive synthesized by the present invention has a self-repairing function, and the self-healing property is particularly remarkable. After heating at 80° C. for 30 minutes, more than 95% of the tensile strength can be restored. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the GPC spectrum of the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention. DETAILED DESCRIPTION
[0024] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0025] The raw materials used in the experiment in the embodiment of the present invention are as follows, but are not limited to the following raw materials. The present invention only uses the following raw materials as specific examples to further illustrate the effect of the detachable structural bonding hot melt adhesive based on multi-functional self-repairing polyurethane described in the present invention:
[0026] Polytetramethylene ether glycol (PTMEG, Mn = 1000 g / mol), isophorone diisocyanate (IPDI), 4,4'-diaminodiphenyl disulfide (AD), dibutyltin dilaurate (DBTDL), 3,4-dihydroxybenzaldehyde (DBD), and N,N-dimethylformamide (DMF) were purchased from Shanghai Adamas Reagent Co., Ltd. (a subsidiary of Shanghai Titan Technology Co., Ltd.).
[0027] The performance testing method in the embodiment of the present invention is as follows:
[0028] Self-healing performance test: The sample was cut into a dumbbell shape for tensile testing. As with the lap shear test, the tensile test was performed at a rate of 100 mm / min. At room temperature, the test strip was cut in the middle and the cut surfaces were assembled together. After the cut samples were repaired at 80°C for different times, the tensile test was performed again to calculate the self-healing rate. The formula is as follows:
[0029]
[0030] Wherein, P represents elongation at break, tensile strength or toughness.
[0031] The present invention sets Examples 1 to 5 to synthesize a series of PU-PADx hot melt adhesives, and the feed ratios are shown in Table 1:
[0032] Table 1
[0033]
[0034] Examples 1 to 5 were prepared according to the following process:
[0035] (1) polytetramethylene ether glycol PTMEG (37.50 mmol, 37.50 g) was put into a reaction kettle, the temperature was raised to 120° C. and vacuum dehydration was carried out for 1 hour, then the temperature was lowered to 80° C., isophorone diisocyanate IPDI (75.00 mmol, 16.67 g) was added and stirred for 1 hour under a nitrogen atmosphere, and finally a formulated amount of catalyst dibutyltin dilaurate DBTDL was added to carry out prepolymerization for 3 hours to obtain a prepolymer;
[0036] (2) Adding a formulated amount of 4,4'-diaminodiphenyl disulfide AD dissolved in N,N-dimethylformamide (DMF) into a reaction kettle until the -NCO peak in FTIR disappears;
[0037] (3) Add a formulated amount of 3,4-dihydroxybenzaldehyde DBD, maintain the reaction at 80°C under a nitrogen atmosphere, pour the uniform viscous liquid into a polytetrafluoroethylene mold after 8 hours, maintain it at 80°C for 48 hours, and then vacuum dry it for 12 hours to obtain PU-PADx hot melt adhesive, wherein x represents the molar ratio of prepolymer to AD in the system.
[0038] The GPC data of the PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention are shown in Table 2:
[0039] Table 2
[0040]
[0041] Note: * stands for dispersion index.
[0042] Depend on Figure 1From the above GPC data in Table 2, it can be seen that Examples 1 to 5 of the present invention successfully synthesized PU-PADx hot melt adhesive.
[0043] The mechanical properties of the PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention were tested, and the results are shown in Table 3:
[0044] Table 3
[0045]
[0046]
[0047] It can be seen from the data in Table 3 that the tensile strength of the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention reaches 11.4 to 24.5 MPa, the elongation at break reaches 234.3 to 743.3%, and the tensile toughness reaches 12.4 to 66.5 MJ / m 3 That is, the PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention have excellent tensile strength, elongation at break, and tensile toughness, which not only highlight their excellent bonding properties in practical applications, but also provide a promising strategy for developing the next generation of tougher materials and adhesives.
[0048] The lap shear strength and debonding work of the PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention and the aluminum substrate were tested, and the results are shown in Table 4:
[0049] Table 4
[0050]
[0051]
[0052] It can be seen from the data in Table 4 that the lap shear strength between the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention and the aluminum substrate reaches 4.25 to 14.23 MPa, and the debonding work reaches 2.20 to 12.50 kN / m, that is, the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention has excellent shear strength and debonding work for the aluminum substrate, especially the PU-PAD1.4 hot melt adhesive of Example 2 has a shear strength of up to 14.23 MPa and a debonding work of up to 12.50 kN / m for the aluminum substrate, which are better than most adhesives reported on the market. The PU-PAD1.4 hot melt adhesive achieves the best balance between cohesion and adhesion, and exhibits the most outstanding performance.
[0053] The lap shear strength of the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention and the aluminum substrate at different temperatures was tested, and the results are shown in Table 5:
[0054] Table 5
[0055]
[0056] It can be seen from the data in Table 5 that the PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention can all exhibit excellent adhesion within the range of 0 to 55°C.
[0057] The PU-PADx hot melt adhesives of Examples 1 to 5 of the present invention were subjected to lap shear tests by repeatedly using aluminum plates. The lap shear strengths after cyclic bonding and debonding are shown in Table 6:
[0058] Table 6
[0059]
[0060] It can be seen from the data in Table 6 that the room temperature aluminum-aluminum shear strength of the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention is 4.25 to 14.23 MPa, and the shear strength retention rate after repeated bonding for 6 times is above 93.04%.
[0061] In order to evaluate the applicability of the PU-PADx hot melt adhesives of Examples 1 to 5, lap shear tests were performed on substrates of different materials. The results are shown in Table 7:
[0062] Table 7
[0063]
[0064]
[0065] It can be seen from the data in Table 7 that the PU-PADx hot melt adhesives 1 to 5 of the present invention exhibit significantly strong adhesion to metal surfaces such as aluminum, steel and iron, as well as wooden boards, can be tightly combined with various metal materials and wooden boards, have a wide range of applicability, and greatly expand the application range of the adhesive.
[0066] The self-healing ability of the PU-PADx hot melt adhesive of Examples 1 to 5 of the present invention was evaluated. Optical microscopy showed that at 80°C, the scratches on the hot melt adhesive of Examples 1 to 5 were almost completely repaired within 30 minutes, indicating that it has efficient self-healing properties. The self-healing efficiency of the stretched sample can be increased to more than 95% within 30 minutes of repair.
[0067] It can be seen that the present invention successfully prepared a series of detachable structural bonding hot melt adhesives (PU-PADx) based on multi-synergistic self-healing polyurethane, which are suitable for various substrates and greatly expand the application range of adhesives. By adjusting the ratio of prepolymer to AD and DBD, the length and aggregation state of the molecular chain are changed, and an effective balance between cohesive energy and adhesion is achieved. Among them, the lap shear strength and debonding work of the hot melt adhesive in Example 2 for aluminum plates reached 14.23MPa and 12.50kN / m respectively. After six repeated bondings, the strength was still as high as 13.24MPa, which is better than most reported reusable adhesives. In addition, PU-PAD1.4 hot melt adhesive exhibits significant strong adhesion to metal surfaces such as aluminum, steel and iron, as well as wooden boards. The excellent adhesion strength comes from metal chelation, hydrogen bonding and electrostatic interactions, and its elongation at break can still reach 643.85% at a tensile strength of 18.34MPa, and the self-healing rate is as high as 98.28%. These properties not only highlight its excellent bonding performance in practical applications but also provide a promising strategy for developing the next generation of tougher materials and adhesives.
Claims
1. A method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane, characterized in that: The steps include: (1) putting polytetramethylene ether glycol or polytrimethylene ether glycol into a reaction kettle, heating to 120° C. and vacuum dehydrating for 1 hour, then lowering the temperature to 80° C., adding isophorone diisocyanate or 4,4-diisocyanate dicyclohexylmethane and stirring for 1 hour under a nitrogen atmosphere, and finally adding a catalyst dibutyltin dilaurate for prepolymerization for 3 hours to obtain a prepolymer; (2) adding 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide dissolved in a diluent into a reaction kettle until the -NCO peak in FTIR disappears; (3) 3,4-dihydroxybenzaldehyde was added, and the reaction was maintained at 80°C under a nitrogen atmosphere. After 8 hours, the uniform viscous liquid was poured into a polytetrafluoroethylene mold, maintained at 80°C for 48 hours, and then vacuum dried for 12 hours to obtain a detachable structural bonding hot melt adhesive based on multi-component synergistic self-healing polyurethane.
2. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane according to claim 1, characterized in that: In step (1), the number average molecular weight Mn of the polytetramethylene ether glycol or polytrimethylene ether glycol is 850 to 1500 g / mol.
3. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane as claimed in claim 2, characterized in that: In step (1), the molar ratio of the polytetramethylene ether glycol or polytrimethylene ether glycol to isophorone diisocyanate or 4,4-diisocyanate dicyclohexylmethane is 1:
2.
4. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane as claimed in claim 2, characterized in that: In step (1), the molar ratio of the polytetramethylene ether glycol or polytrimethylene ether glycol to the catalyst dibutyltin dilaurate is 1:
10. -5 .
5. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane as claimed in claim 1, characterized in that: In step (2), the diluent is a mixture of one or more of N,N-dimethylformamide, cyclohexanone, N,N-dimethylacetamide, and N-methylpyrrolidone, and the mass ratio of 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide to the diluent is 1:
4.
6. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane as claimed in claim 1, characterized in that: In step (2), the molar ratio of the prepolymer to 4,4'-diaminodiphenyl disulfide or 2,2'-diaminodiphenyl disulfide is 1:1.2-2.
0.
7. The method for synthesizing a detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane as claimed in claim 1, characterized in that: In step (3), the molar ratio of the prepolymer to 3,4-dihydroxybenzaldehyde is 1:0.4-2.
0.
8. A detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane, characterized in that: The hot melt adhesive is prepared by the synthesis method described in any one of claims 1 to 7.
9. The detachable structural bonding hot melt adhesive based on multi-component synergistic self-repairing polyurethane according to claim 8, characterized in that: The room temperature aluminum-aluminum shear strength of the hot melt adhesive is 4.25-14.23 MPa, the shear strength retention rate after repeated bonding for 6 times is more than 93.04%, and it exhibits excellent mechanical properties at 0-55°C and on a variety of substrates, with a tensile strength of 11.4-24.5 MPa, an elongation at break of 234.3-743.3%, and a tensile toughness of 12.4-66.5 MJ / m 3 , treated at 80℃ for 30 minutes, the self-healing efficiency of tensile strength reached more than 95%.
Citation Information
Patent Citations
Transparent high strength and high toughness room temperature self-repairing thermoplastic polyurethane urea elastomer and preparation method
CN110105534A
Self-healing polymer-bonded explosive and preparation method thereof
CN115819159A
Self-repairing polyurethane as well as preparation method and application thereof
CN116284673A
Preparation method of self-repairing polyurethane based on disulfide bonds
CN118221907A
Self-repairable, repeatedly-processed and degradable polyurethane material based on multi-bond action and preparation method of self-repairable, repeatedly-processed and degradable polyurethane material
CN118930793A